2021
DOI: 10.3389/fped.2021.696499
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Cardiovascular Complications in Type 1 Diabetes: The Need for a Lifetime Approach

Abstract: Cardiovascular disease (CVD) remains the main cause of morbidity and mortality in individuals with type 1 diabetes (T1D). Adolescence appears to be a critical time for the development of early subclinical manifestations of CVD, with these changes likely driven by a deterioration in glycemic control during the progression through puberty, combined with the emergence of numerous other traditional cardiometabolic risk factors (e.g., hypertension, dyslipidemia, smoking, alcohol use, obesity, etc.) which emerge at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Subjects with type 1 diabetes are at higher risk of coronary heart disease (CHD) including acute myocardial infarction (AMI) [ 2 5 ], and cardiovascular disease (CVD) is the main cause of death in adults with type 1 diabetes [ 6 8 ]. International diabetes guidelines recommend aggressive management of modifiable cardiovascular risk factors as individuals with type 1 diabetes have generally higher risk of CVD, and the risk is increased in those diagnosed at an early age [ 9 12 ]. Studies from Finland and Sweden have shown a greater decline in the incidence of CVD in subjects with type 1 diabetes over time compared to the general population [ 3 , 4 , 13 ], while an American study did not find time-trends in CHD by age at diagnosis (1965–1980) of childhood-onset type 1 diabetes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with type 1 diabetes are at higher risk of coronary heart disease (CHD) including acute myocardial infarction (AMI) [ 2 5 ], and cardiovascular disease (CVD) is the main cause of death in adults with type 1 diabetes [ 6 8 ]. International diabetes guidelines recommend aggressive management of modifiable cardiovascular risk factors as individuals with type 1 diabetes have generally higher risk of CVD, and the risk is increased in those diagnosed at an early age [ 9 12 ]. Studies from Finland and Sweden have shown a greater decline in the incidence of CVD in subjects with type 1 diabetes over time compared to the general population [ 3 , 4 , 13 ], while an American study did not find time-trends in CHD by age at diagnosis (1965–1980) of childhood-onset type 1 diabetes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, atherosclerosis has been observed as early as 6 years after type 1 diabetes onset,26 and in youth and young adults 27 28. Individuals with early onset type 1 diabetes are therefore exposed to risk factors for years before interventions take place 29. The heterogeneity in recommendations across guidelines, particularly for the different age groups, cannot be overlooked as they lead to varying management strategies.…”
Section: Discussionmentioning
confidence: 99%
“… 27 28 Individuals with early onset type 1 diabetes are therefore exposed to risk factors for years before interventions take place. 29 The heterogeneity in recommendations across guidelines, particularly for the different age groups, cannot be overlooked as they lead to varying management strategies. The use of diabetes duration as a risk factor in the NICE guidelines helps to capture young individuals with type 1 diabetes in the prevention of CVD, 30 whereas the Dutch guideline uses presence of diabetes-related complications that may present before CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with type 1 diabetes (T1D) are at risk for morbidity and mortality as a result of diabetes-related complications. 1 Although there has been an overall improvement in life expectancy and quality of life over the years, there is still a discrepancy of 11-13 years in life expectancy in individuals with T1D in comparison to controls without diabetes. 2 This reduction in life expectancy remains largely attributed to cardiovascular disease (CVD).…”
mentioning
confidence: 99%
“…3 Although glycemic control is the cornerstone for T1D management, studies have shown that both lipid and blood pressure levels also affect the development of micro-and macrovascular complications. 1,4 Moreover, dyslipidemia and hypertension have been hypothesized to have synergistic effects in cardiovascular risk. 5 Lowering blood pressure, and to a lesser extent low-density lipoprotein-cholesterol (LDL-c), has been shown to have protective effects against CVD in individuals with T1D.…”
mentioning
confidence: 99%